Teachers’ Experiences Using ChatGPT for Lesson Planning in EFL Classrooms - Sirniawati Sirniawati; Azran Azmee (CV. Akademi Merdeka, 2025)
This qualitative study explores EFL teachers’ experiences using ChatGPT for lesson planning, focusing on both practical interactions and reflective perceptions. Through semi-structured interviews with eight teachers, the research investigates how ChatGPT influences lesson design, professional identity, and pedagogical thinking. Findings reveal that ChatGPT enhances efficiency by providing immediate access to diverse resources and stimulates creativity by suggesting novel teaching ideas. However, teachers also face challenges related to the contextual relevance and accuracy of AI-generated content, requiring critical evaluation and adaptation to align with local curricula and student needs. Additionally, teachers experience a shift in professional identity, viewing themselves as collaborators with AI rather than sole content creators. This shift fosters deeper pedagogical reflection and more flexible lesson design practices. At the same time, concerns about over-dependence on AI and the potential loss of authenticity highlight important ethical and professional considerations. The study emphasizes the need for balanced and critical engagement with AI tools in EFL teaching, advocating for teacher training programs that address both technical and ethical dimensions. The findings contribute to understanding the complex role of AI in language education and suggest directions for future research on AI-supported teaching practices.